Size effect and age factor in mechanical properties of BST Light Weight Concrete. (20th July 2018) - Vakhshouri, Behnam; Nejadi, Shami
Highlights: Fracture mechanics is the basic principle in studying the size effect. Size effect (scaling factor) and shape effect are not investigated in EPS-LWC. Different shape and size of test specimens are used in this study. Experimental values of compressive and splitting tensile strength are evaluated. Existing models of size effect of LWC conventional concrete are investigated. Age factor in compressive and splitting tensile strength of EPS-LWC are proposed. Effect of shape and size of test specimens on EPS-LWC properties are modeled. Abstract: Replacement of whole or part of normal aggregates with Expanded Polystyrene (EPS) beads in the concrete mix is a reliable method to produce Light Weight Concrete (LWC) with considerable advantages. Due to modification effect on mechanical properties of LWC, it is important to examine whether all the assumed hypotheses about conventional concrete also are applicable for LWC structures. Based on an experimental program, this study investigates the effects of specimen size and shape on the compressive and tensile strength of this type of LWC. In this regard, cylinder specimens with 75 × 150, 100 × 200 and 150 × 300 mm dimensions and cube specimens with 100 and 150 mm dimensions were cast and cured in laboratory conditions. Compressive and tensile strengths were tested after 3, 7, 14, 21, 28, 56 and 91 days. The correlation factor between the compressive strength, tensile strength and the shape and size of specimens is evaluated also.